2010
DOI: 10.1007/s12274-010-1026-0
|View full text |Cite
|
Sign up to set email alerts
|

Shape-controlled synthesis of Mn3O4 nanocrystals and their catalysis of the degradation of methylene blue

Abstract: Various sizes and shapes of Mn 3 O 4 nanocrystals have been prepared in a one-pot synthesis in extremely dilute solution by soft template self-assembly. To better control size and shape, the effects of varying the growth time, reaction temperature, surfactant, and manganese source were examined. The average size of octahedral Mn 3 O 4 crystallites was found to be related to the reaction time, while higher reaction temperature (150 °C ) and the use of a cetyltrimethylammonium bromide/poly(vinylpyrrolidone) (CTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 57 publications
8
70
0
Order By: Relevance
“…In the spectrum, the characteristic peak of MB at 664 was found which is in good agreement with the reported earlier values [31]. As the reaction time was prolonged, the reaction solution gradually turned colorless and the original absorption maximum at 664 nm was gradually decreased and shifted to shorter wavelength [17,18] indicating that MB was oxidized by Mn 3 O 4 . Zaied et al (2011) found the presence of intermediate reaction products, azure A (AA), azure B (AB), azure C (AC), and thionine (Th) during the degradation of MB using manganese oxide and the corresponding characteristic UV-vis λ max was identified as 628, 638, 618, and 601 nm, respectively [32].…”
Section: Spectra Of Uv-vis Wavelength Scansupporting
confidence: 89%
See 2 more Smart Citations
“…In the spectrum, the characteristic peak of MB at 664 was found which is in good agreement with the reported earlier values [31]. As the reaction time was prolonged, the reaction solution gradually turned colorless and the original absorption maximum at 664 nm was gradually decreased and shifted to shorter wavelength [17,18] indicating that MB was oxidized by Mn 3 O 4 . Zaied et al (2011) found the presence of intermediate reaction products, azure A (AA), azure B (AB), azure C (AC), and thionine (Th) during the degradation of MB using manganese oxide and the corresponding characteristic UV-vis λ max was identified as 628, 638, 618, and 601 nm, respectively [32].…”
Section: Spectra Of Uv-vis Wavelength Scansupporting
confidence: 89%
“…It can be seen from the result that at medium pH greater than 4 (higher than that of pH pzc ), MB was not oxidized by Mn 3 O 4 [34]. Moreover, in neutral and alkali media, there was hardly any decolorization of MB [17,18].…”
Section: Effect Of Medium Ph On Mb Degradationmentioning
confidence: 91%
See 1 more Smart Citation
“…The specific surface area and porosity of three different Fe 3 O 4 @MnO 2 composite microspheres were determined by N 2 adsorption-desorption isotherms shown in the Figure 6. According to the IUPAC classification, all of three graphics display a type IV isotherm with a H3-type hysteresis loop (P/P 0 > 0.4), indicating the formation of pores [34]. Moreover, the sharp increment of N 2 adsorption amount on the three isotherms at the relative pressure P/P 0 = 0.92-1.0 demonstrates the existence of macroporosity.…”
Section: Resultsmentioning
confidence: 94%
“…Compared with traditional separation technologies such as centrifugation and filtration, magnetic separation through an external magnetic field is more convenient and less cost-intensive [16]. Magnetite (Fe 3 O 4 ) nanoparticles are prevalently employed as magnetic cores owing to their outstanding magnetic and electrochemical properties [17][18][19][20]. However, their high surface area to volume ratio and strong dipole-dipole attraction make them prone to aggregation, and the limited functional groups circumvent their further applications [16].…”
Section: Introductionmentioning
confidence: 99%